Seeds of discovery : how Barbara McClintock used corn and curiosity to solve a science mystery and win a Nobel prize - Alexander, Lori (Clarion Books, an imprint of HarperCollinsPublihsers, 2025)
"As a rare female botanist in early twentieth-century America, Barbara McClintock never let other people's notions of what was proper slow her down. When she faced doubting colleagues and unsupportive institutions, she drove across the United States, climbed through windows, and even slept in her laboratory to conduct her research. In so doing, she helped pave the way for future scientific discoveries that can cure diseases and save lives -- and won a Nobel Prize in the process!" --